Murder Point: A Tale of Keewatin - Dawson, Coningsby, 1883-1959 (Salt Lake City, UT : Project Gutenberg, 2009)
"Murder Point: A Tale of Keewatin" by Coningsby Dawson is a novel written in the early 20th century. The story centers on John Granger, an independent trader isolated in the rugged wilderness of northern Canada, as he grapples with feelings of loneliness and despair while reflecting on his past decisions. The narrative hints at themes of regret, madness, and the heavy weight of personal history, creating a backdrop rich with tension and anticipation. At the start of the book, we meet John Granger, who sits in his store at Murder Point, contemplating his unfulfilled life and the stark wilderness around him. The oppressive silence of Keewatin presses on him, stirring up unwanted memories of his life in London, causing him to question whether he has made a mistake in choosing this secluded existence. As he reflects, he is suddenly drawn back to the present by the appearance of a mysterious stranger, who turns out to be his old friend Spurling, arriving in a state of panic and urgency. Their reconnection sets the stage for a complex exploration of their shared past in the Klondike and the dark undercurrents of guilt and betrayal that threaten to consume them both. (This is an automatically generated summary.)
Release date is 2009-07-13
E-text prepared by David T. Jones and the Project Gutenberg Online Distributed Proofreading Canada Team (http://www.pgdpcanada.net) from digital material generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana) and the Google Books Library Project (http://books.google.com/intl/en/googlebooks/library.html)
Keywords: Fiction; Detective and mystery stories